N-Glycosylation of the SARS-CoV-2 Receptor Binding Domain Is Important for Functional Expression in Plants - Shin, Yun-Ji; König-Beihammer, Julia; Vavra, Ulrike; Schwestka, Jennifer; Kienzl, Nikolaus F.; Klausberger, Miriam; Laurent, Elisabeth; Grünwald-Gruber, Clemens; Vierlinger, Klemens; Hofner, Manuela; Margolin, Emmanuel; Weinhäusel, Andreas; et al. (Frontiers in Plant Science, 2021)
Nicotiana benthamiana is used worldwide as production host for recombinant proteins. Many recombinant proteins such as monoclonal antibodies, growth factors or viral antigens require posttranslational modifications like glycosylation for their function. Here, we transiently expressed different variants of the glycosylated receptor binding domain (RBD) from the SARS-CoV-2 spike protein in N. benthamiana. We characterized the impact of variations in RBD-length and posttranslational modifications on protein expression, yield and functionality. We found that a truncated RBD variant (RBD-215) consisting of amino acids Arg319-Leu533 can be efficiently expressed as a secreted soluble protein. Purified RBD-215 was mainly present as a monomer and showed binding to the conformation-dependent antibody CR3022, the cellular receptor angiotensin converting enzyme 2 (ACE2) and to antibodies present in convalescent sera. Expression of RBD-215 in glycoengineered XT/FT plants resulted in the generation of complex N-glycans on both N-glycosylation sites. While site-directed mutagenesis showed that the N-glycans are important for proper RBD folding, differences in N-glycan processing had no effect on protein expression and function.